Developing intermediate zones for analysing the social geography of Auckland, New Zealand. (17th March 2016) - Zhao, Jinfeng; Exeter, Daniel J.
Abstract : This paper describes the creation of two new geographical boundary files, known respectively as lower zones and upper zones, for investigating social phenomena and visualising disparities in health outcomes in the Auckland Region of New Zealand. We test the effectiveness of contemporary automated zone design tools before applying an interactive approach which integrated computational power with expert local knowledge and visual interpretation to develop meaningful zones. We demonstrate that an interactive approach addresses multiple zone design criteria (e.g. respecting physical barriers, compactness and homogeneity) more effectively than is possible with an automated approach.